Persepsi Masyarakat terhadap Profesi Guru - Suharjo Dwijosumarto (Universitas Negeri Malang, 2016)
The purpose of this study was to find out the perception and suggestion of the community to the improvement of teaching profession. The research was carried out at Margopatut, Nganjuk. The respondents were 18 government employees and 24 farmers and businessmen. Data were gathered by documentation, observation and interview and analysed qualitatively. The results indicate that more than 80% respondents have good perception about teaching profession